Phylogeny and new species of the genus Lipurometriocnemus Sæther (Diptera: Chironomidae) - Donato, Mariano Humberto (2019)
Lipurometriocnemus Sæther (Diptera: Chironomidae: Orthocladiinae) is composed of fve species endemic to the Americancontinent. Three new species from Argentina are described and illustrated as males and Austrocladius barilochensis (Edwards) is newlytransferred to Lipurometriocnemus. A cladistic analysis of Orthocladiinae placed Lipurometriocnemus as sister group to Metriocnemus vander Wulp. A separate cladistic analysis of Lipurometriocnemus species was also conducted and the results are discussed. An identifcationkey to the adult males of Lipurometriocnemus is provided.